A comparison of mechanical properties of recycled high‐density polyethylene/waste carbon fiber via injection molding and 3D printing. Issue 4 (23rd February 2022) - Borkar, Ameya; Hendlmeier, Andreas; Simon, Zan; Randall, James D.; Stojcevski, Filip; Henderson, Luke C.
Abstract: Recycled high‐density polyethylene (r‐HDPE) was combined with waste carbon fiber by loading 6 k, 12 k, and 24 k tows through an extruder to create thermoplastic/carbon pellets with fiber volume fractions of 11.2%, 18.9%, and 29.5%, respectively. Tensile and flexural coupons were subsequently produced via injection molding and novel 3D printing. The addition of carbon into r‐HDPE in all cases showed increased mechanical properties. Maximum increases were observed through the inclusion of 29.5% fiber volume fraction. Increases in tensile and flexural modulus of up to 2.9 GPa (+505.9%) and 5.8 GPa (+711.0%) respectively were observed for r‐HDPE/carbon fiber (CF) samples. Increases in tensile and flexural strengths of up to 57.9 MPa (+311.8%) and 47.7 MPa (+188.0%) respectively were observed for 29.5% r‐HDPE/CF samples. Some variance in mechanical performance between injection molded and 3D printed samples was observed indicating production methodology might influence final material performance. Abstract :